PERSEPSI MAHASISWA TERHADAP PENERAPAN PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA (MBKM): PERTUKARAN MAHASISWA MERDEKA ANTAR PROGRAM STUDI (Jurnal Biogenerasi, 2023)
This research aims to observe student’s perceptions toward the implementation of MBKM, students exchange between study program at Institut Turatea Indonesia. The instruments used were questionnaires and interviews. Questionnaires were distributed to fiftth semester students as many as 65 students who were referred to as respondents. The questionnaire that was distributed covered two main aspects: first, to capture respondents' perceptions of the MBKM program, second, to capture respondents' perceptions of the implementation of the independent student exchange program between study programs. Based on the results of questionnaire analysis and interviews, it was obtained that the results of student perceptions in the MBKM program were at a percentage of 79% (good category) and student perceptions of the independent student exchange program between study programs were at a percentage of 89% (very good category).
Keywords: Perception; MBKM; students exchange between study program